Phylogenetic Analysis of the Spiny Oryctocephalids (Trilobita, Corynexochida?, Oryctocephalidae), Cambrian. (May 2014) - Sundberg, Frederick A.
Abstract : Phylogenetic analyses of the Cambrian spiny oryctocephalids support the elevation to familiar rank of Oryctocephalidae Beecher, 1897 and indicate that the family can be divided into two clades, here designated as the subfamilies Oryctocephalinae Beecher, 1897 and Lancastriinae Kobayashi, 1935. Curvoryctocephaliinae Zhao and Yuan in Yuan et al., 2002 is considered here a junior synonym of Lancastriinae. Oryctocephalinae have tapered or parallel sided glabella and is composed of species of Oryctocephalus Walcott, 1886. The subgenera Oryctocephalus ( Oryctocephalus ) and O . ( Eoryctocephalus ) Zhao and Yuan in Yuan et al., 2002 do not form separate clades and are here rejected. The genera of the Lancastriinae have expanding glabellae. The subfamily is composed of a broad variety of genera that can be divided into three major subclades: Lancastria, Protoryctocephalus, and Oryctocephalites . The Lancastria subclade is composed of Lancastria Kobayashi, 1935, Changaspis Lee in Chien, 1961, and Goldfieldia Palmer, 1964 occurring at the base of the Lancastriinae. Goldfieldia and Lancastria form a sister group to Changaspis . The long branches in the phylograms indicated significant differences between these taxa; thus, the genus Goldfieldia is maintained. The Protoryctocephalus subclade is monogeneric and forms a sister group to the Oryctocephalites subclade. The Oryctocephalites subclade consists of several species of this genus and the more derived forms Metabalangia Qian and Yuan in Zhang et al., 1980 and Tonkinella Mansuy, 1916. Oryctocephaloides Yuan in Zhang et al., 1980 is considered a junior synonym of Oryctocephalites Resser, 1939. The subgenera Oryctocephalites ( Oryctocephalites ) and O . ( Parachangaspis ) Zhao and Yuan in Yuan et al., 2002 do not form separate clades. The later subgenus occurs in the basal portion of the Oryctocephalites subclade indicating that it is a paraphyletic taxon. Opsiosoryctocephalus Sundberg, 1994, Oryctocephalops Lermontova, 1940, and Curvoryctocephalus Zhao and Yuan in Yuan et al., 2002 are not consistent in their placement within the phylogenetic analyses, although they always occur in the Lancastriinae. As a result they are not placed within a subclade within Lancastriinae. The type species Goldfieldia pacifica Palmer, 1964 was based solely on cranidia. This species is redescribed using topotype material that includes cranidia, librigenae, hypostomes, thorax, and pygidia.